A New Strategy to Synthesize α, ω‐Dihydroxy Multiblock Copolymers via [CpRu(CH3CN)3]PF6/Quinaldic Acid Catalyst. Issue 17 (5th September 2019) - Zhu, Xiuzhong; Wang, Zichao; Liu, Jie; Min, Xin; Wang, Tong; Fan, Xiaodong
Abstract : Inside Back Cover : In article number1900135, Xiaodong Fan and co‐workers report a new strategy to synthesize random and alternating multiblock copolymers (MBCs) via polycondensation of terminal hydroxyl groups in macromolecular monomers.